IDENTIFICATION OF VARIABLES AFFECTING ACCESS TO IMPROVED DRINKING WATER SOURCES IN INDONESIA - Dipa Wardhana, Adha
Drinking water is a basic human need, however, according to WHO, only 5.8 billion people (about 74% of the world's population) in 2020 have access to safely managed drinking water services. Indonesia as a developing country has no better conditions, where in 2018 total access to proper drinking water sources was 87.8%, and in urban areas only 51.5%. In order to achieve the Sustainable Development Goals (SDGs) target, namely 100% access to adequate drinking water sources by 2030, the variables affecting access to improved drinking water sources in Indonesia are needed to understand, so that government intervention can be more focused. In contrast to previous studies which always used sampling based household survey data, this research was conducted using population based statistical data issued by the state statistical agency. This research was conducted to determine the variables that affect access to improved drinking water sources in Indonesia, which were analysed using multiple linear regression methods. The results showed that people's access to improved drinking water sources in Indonesia was significantly influenced by city type and size, household size, and gender (as measured by the ratio of males to females). Even though it uses different types of data, the results of this study are still in line with previous studies.